Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Lignin-carbohydrate complexes from sugarcane bagasse: preparation, purification, and characterization - Singh, R.; Singh, S.; Trimukhe, K. D.; Pandare, K. V.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Lignin-carbohydrate complexes were isolated from sugarcane bagasse by a process, which yielded sulfur-free lignins. These could be made carbohydrate-free, if necessary, by treatment with xylanase enzyme. A study of the preparation, purification, and characterization of such lignin-carbohydrate complexes, comparison with commercial lignin samples (wood based as well as bagasse based) and some other lignin derivatives was made by using a variety of analytical tools such as FTIR, HPLC at three different UV-wavelengths, GPC, thermal analysis and elemental analysis. The use of such a diverse range of lignin-carbohydrate complex samples enabled us to predict the sensitivity of the various analytical techniques for characterization of complex polymers containing carbohydrate moieties. Evidence for lignin-carbohydrate complex was detectable by FTIR as well as HPLC studies. Thermal analysis studies showed the crucial effect of carbohydrate groups, the content of aliphatic chains, and the sulfur content of the lignins. Generalized structures of lignin-carbohydrate complexes obtained from various sources using different preparation methods and chemical modifications are presented. This will aid the applications development effort with advantageously using lignins containing low levels of carbohydrate moieties as reactive sites as well as biodegradability inducing sites. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: biodegradability; hardwood lignins; lignin-carbohydrate complex; softwood lignins; Sugarcane bagasse; sulfur-free lignins; xylanase enzyme

Lactic acid production from waste sugarcane bagasse derived cellulose - Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2007)
Production of L(+) lactic acid from sugarcane bagasse cellulose, one of the abundant biomass materials available in India, was studied. The bagasse was chemically treated to obtain a purified bagasse cellulose sample, which is much more amenable to cellulase enzyme attack than bagasse itself. This sample, at high concentration (10%), was hydrolyzed by cellulase enzyme preparations (10 FPU g(-1) cellulose) derived from mutants generated in our own laboratory. We obtained maximum hydrolysis (72%), yielding glucose and cellobiose as the main end products. Lactic acid was produced from this bagasse cellulose sample by simultaneous saccharification and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus delbrueckii mutant Uc-3. A maximum lactic acid concentration of 67 g l(-1) was produced from a concentration of 80 g l(-1) of bagasse cellulose, the highest productivity and yield being 0.93 g l(-1) h(-1) and 0.83 g g(-1), respectively. The mutant Uc-3 was found to utilize high concentrations of cellobiose (50 g l(-1)) and convert it into lactic acid in a homo-fermentative way. Considering that bagasse is a waste material available in abundance, we propose to valorize this biomass to produce cellulose and then sugars, which can be fermented to products such as ethanol and lactic acid.

Metal complexes of crosslinked chitosans. part II. an investigation of their hydrolysis to chitooligosaccharides using chitosanase - Trimukhe, K. D.; Bachate, S.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2007)
This paper investigates the behavior of crosslinked chitosans and metal-complexed crosslinked chitosans under similar hydrolytic conditions. Crosslinked chitosans with trimellitic anhydride, diisocyanatohexane, and dibromodecane as crosslinking agents under heterogenous reaction conditions were used as metal complexing agents by equilibrating them with metal salts such as ZnCl2, MnSO4, CuSO4, CdSO4, Pb(NO3)(2), and HgCl2. Crosslinked chitosan without metal complexation had the same hydrolytic behavior as uncrosslinked chitosan. However, when the crosslinked chitosans were complexed with metals, their rates of hydrolysis and extent of hydrolysis were significantly reduced. Thus, while for chitosan about 840 mu g/ml reducing sugar was produced in 4 h time, and 780 mu g/ml was produced for diisocyanatohexane crosslinked chitosan, only 400 mu g/ml and 320 [mu g/ml reducing sugars were produced for cadmium sulfate with crosslinked chitosan and diisocyanatohexane crosslinked chitosan, respectively. Similar results are obtained for other crosslinking agents. Studies on preincubation of the metal with the enzyme show that of the metals studied, Mn has no effect on preincubatioin with the enzyme, Hg, Cd, Pb, and Cu completely deactivates the enzyme, while Zn reduces the enzyme activity by about 43.3%. Preincubation of the metal salts with the chitosan shows that Hg and Cu completely deactivate the molecule from enzyme hydrolysis, Cd and Zn inactivate it to the extent of 56.8% and 43.3%, respectively, while Mn has no effect. Availability of the amino functions seems to be a key feature for the chitosanase to hydrolyze the chitosan polymer. This was also proved by the significant increase in the extent of hydrolysis for chitosan samples with 88% (final value 1120 mu g/ml reducing sugar) and 85% deacetylation (final value 840 mu g/ml reducing sugar). HPIC studies of the products show that a variety of oligomers are produced in the chitosanase enzyme hydrolytic reaction. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: chitooligosaccharides; Chitosan; chitosanase hydrolysis; Crosslinked chitosan; metal-complexed crosslinked chitosan

Strain improvement of penicillium janthinellum ncim 1171 for increased cellulase production - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Varma, Anjanikumar; Gokhale, D. V. (Bioresource Technology, 2007)
The strain of Penicilhuinjanthinellunt NOM 1171 was subjected to mutation involving treatment of Ethyl Methyl Sulfonate (EMS) for 24 h followed by UV-irradiation for 3 min. Successive mutants showed enhanced cellulase production (EMS-UV-8), clearance zone on Avicel containing plate (SM2) and rapid growth on Walseth cellulose agar plates containing 0.2% 2-deoxy-D-glucose (SM3). These mutants were transferred to Walseth cellulose plates containing higher concentration (1.5%) of 2-deoxy-D-glucose (SM4) in which only five mutants showed clearance zone on SM4. All these mutants showed approximately two-fold increase in activity of both FPase and CMCase in shake flask culture when grown on basal medium containing CP-123 (1%) and wheat bran (2.5%). The enzyme preparations from these mutants were used to hydrolyze Avicel. Higher hydrolysis yields of Avicel were obtained with enzyme preparations of EU1. This is the first report on the isolation and selection of mutants based on hydrolysis of Avicel, which is the most crystalline substrate. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 2-deoxy-D-glucose resistant mutants; cellulase activity; EMS and ultraviolet mutation; Penicillium janthinellum

Sugar-linked biodegradable polymers: regio-specific ester bonds of glucose hydroxyls in their reaction with maleic anhydride functionalized polystyrene and elucidation of the polymer structures formed - Galgali, P.; Agashe, M.; Varma, Anjanikumar (Carbohydrate Polymers, 2007)
In the development of sugar-linked synthetic polymers as biodegradable polymers, it is imperative to know the variety of polymer structures formed by the reaction of a multi-functional sugar molecule with the functionalized synthetic polymer on which the sugar is to be anchored. Enzymes produced by the microorganisms causing the polymer to biodegrade can be sensitive to the particular type of sugar hydroxyl utilized (such as anomeric, primary, or secondary hydroxyl group) for getting anchored to the polymer. In this paper, we present synthesis of regio-specific ester derivatives of glucose with anhydride, functionalized polymers, i.e., ester formation specifically with the anomeric, primary or secondary hydroxyls of glucose. Characterization of these different esters groups was done using FTIR spectroscopy; each ester peak was further deconvoluted to yield its different components. For this purpose, we studied the reactions of D-glucose, 6-O-trityl glucose, methyl glucoside, 1,2-5,6-diisopropylidene-D-glucose, and 1,2,3,4-tetraacetyl-D-glucose with maleic anhydride functionalized polystyrene (PSMAH). In this study, the primary hydroxyl of glucose was found to be even more reactive than the anomeric hydroxyl. The peaks at similar to 1716, similar to 1725, and 1729-1737 cm(-1) were assigned to the ester carbonyl of the anomeric, primary, and secondary hydroxyls of glucose (C2, C3, and C4), respectively. An attempt was made to quantify the extent to which the different polymer structures are formed in a particular reaction by taking ratios of non-variable reference peaks (polystyrene peak at 1493 cm-1) and variable peaks caused by the reaction (the residual anhydride carbonyl at 1780 cm(-1)). (c) 2007 Published by Elsevier Ltd.
Keywords: Biodegradable polymers; functionalized synthetic polymer; glucose; regio-specific; sugar-linked polystyrene

Complexation of heavy metals by crosslinked chitin and its deacetylated derivatives - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Chitin was crosslinked using diisocyanatohexane (HDI), trimellitic anhydride (TMA), and dibromodecane (DBD), then deacetylated in strong aqueous alkali. This led to a product with amine functional groups on the exposed surface of the crosslinked chitin, which could be utilized for complexation with heavy metals. Thus, a key feature of the crosslinked derivatives prepared was that only the hydroxy Groups were utilized in the crosslinking reaction, and the acetylamino groups of chitin were hydrolyzed only after the crosslinking was accomplished. This ensured that all amino groups of the chitosans so produced would be available for metal complexation, and not partially used up in crosslinking. This proposed advantage was proved by the similar binding observed for heavy metals like Hg (348-372 mg/g), Cu (91-119 mg/g), Zn (71-92 mg/g), Mn (3-10 mg/g), Cd (121-160 mg/g), and Pb (32-86 mg/g) using these crosslinked polymers, whereas the control polymer (uncrosslinked chitosan powder) had complexation values for Hg (348-361 mg/g), Cu (100-106 mg/g), Zn (81-92 mg/g), Mn (4-7 mg/g), Cd (135 mg/g), and Pb (25-59 mg/g). Additionally, in a case where chitosan was crosslinked with HDI. the amino groups were consumed in the crosslinking reaction, and the metal complexation capacity has found to be decreased for Cu (91-109 mg/g), Cd (133 mg/g), and Zn (71-77 mg/g), while remaining nearly the same for Hg (362 mg/g). The literature value for Cu complexation is 59.67 mg/g for chitosan crosslinked with glutaraldehyde. The crosslinked derivatives have the added advantage of insolubility even in low pH aqueous media, making their repeated re-use possible. Further, these crosslinked derivatives could be used in powder form, and the additional step of preparing beads was found to be not necessary for ease of separation of the crosslinked powder by filtration. The binding capacity of various crosslinked chitin and deacetylated derivatives for Cu, Cd, Hg, Zn, Mn. and Pb was in the region of 100, 140, 360 88, 5, and 60 mg/g (rounded off values) of polymer, respectively, very close to the values obtained for uncrosslinked chitosan. The metal binding for crosslinked chitosan was slightly lower than that of crosslinked chitin and deacetylated derivatives, due to use of some amino groups in crosslinking. For Cu ions, the Langmuir equation was found to be the best fit for HDI crosslinked deacetylated chitin and TMA crosslinked deacetylated chitin. The morphological studies conducted using WAXRD are in close agreement with the metal complexation data, showing complete loss of original chitosan peaks for the heavily complexed derivatives, and minor changes for the weakly complexed metals. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; deacetylated chitin; metal complexation; Morphology

Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification

Morphological study of heavy metal complexes of chitosan and crosslinked chitosans by SEM and WAXRD - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2008)
Metal complexes of salts of Hg, Cu, Cd, Pb, Zn, and Mn with chitosan and crosslinked chitosans were prepared, and their morphologies were studied using scanning electron microscopy and wide angle X-ray diffraction. The metal ions which were specifically and strongly complexed to the amino functions of chitosans, like Hg, showed smooth surface morphology inspite of large number of ions complexed (372 mg/g of chitosan). The presence of metal ions on the surface of the chitosans could be detected with decrease in metal ion binding, in the following sequence Hg > Cu > Cd > Zn > Pb > Mn. Particularly in the case of Pb ions, the presence of these ions is clearly seen on the surface of the polymer by SEM. The number of ions of Mn complexed on the polymers was too few (5 mg/g of chitosan) to be visible. SEM of Hg and Cu complexes do not show the ``holes'' observed in the crosslinked polymers as they bind specifically to amino groups of chitosan, but for Cd, Zn, Mn, and Pb complexes, these ``holes'' are clearly visible. These results are also in agreement with the morphologies studied by WAXRD. The metal complexation data for each of these metal ions was also in the same sequence. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; metal complex; Morphology; SEM; WAXRD

Cellulases from penicillium janthinellum mutants: solid-state production and their stability in ionic liquids - Adsul, Mukund G.; Terwadkar, Asawari P.; Varma, Anjanikumar; Gokhale, Digambar V. (Bioresources, 2009)
The cellulase production by P. janthinellum mutants on lignocellulosic material such as cellulose or steam exploded bagasse (SEB) in combination with wheat bran was studied in solid state fermentation (SSF). One of the mutants, EU2D21, produced the highest levels of endoglucanase (3710 IU g(-1) carbon source) and beta-glucosidase (155 IU g(-1) carbon source). Ionic liquids are so-called green solvents that have become attractive for biocatalysis. Stability of mutant cellulases was tested in 10-50% of the ionic liquid 1-butyl-3-methylimidazolium chloride ([bmim]Cl). FPA and CMCase were significantly stable in 10% ionic liquid after 5h. beta-glucosidase showed 85% of its original activity after 5 h incubation in 30% ionic liquid and retained 55% of its activity after 24 h. This enzyme preparation hydrolyzed ionic-liquid-treated SEB completely in 15 h in the presence of 20% ionic liquid. These studies revealed that there is no need of regenerating cellulose after ionic liquid treatment, since cellulase of mutant strain was found to be significantly stable in the ionic liquid.
Keywords: Cellulase stability; Ionic liquid; Mutant cellulase; Solid state fermentation

Hydrolysis of cellulose derived from steam exploded bagasse by penicillium cellulases: comparison with commercial cellulase - Singh, Rajkumar; Varma, Anjanikumar; Laxman, Ryali Seeta; Rao, Mala (Bioresource Technology, 2009)
A complete cellulase from Penicillium pinophilum was evaluated for the hydrolysis of a-cellulose derived from steam exploded sugarcane bagasse and other cellulosic substrates. alpha-Cellulose at 1% substrate concentration was completely hydrolyzed by Penicillium cellulase within 3 h wherein at 10% the hydrolysis was 100% within 24 h with an enzyme loading of 10 FPU/g. The hydrolysate yielded glucose as major end product as analyzed by HPLC. Under similar conditions, hydrolysis of Sigmacell (microcrystalline cellulose), CP-123 (pulverized cellulose powder) and ball milled Solka Floc were 42%, 56% and 52%, respectively. Further the hydrolysis performance of Penicillium sp. cellulase is compared with Trichoderma reesei cellulase (Accellerase (TM) 1000) from Genencore. The kinetics of hydrolysis with respect to enzyme and substrate concentration will be presented. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Accellerase (TM) 1000; Enzymatic hydrolysis; High beta-glucosidase; Penicillium cellulase; Sugarcane bagasse

Metal complexes of crosslinked chitosans: correlations between metal ion complexation values and thermal properties - Trimukhe, K. D.; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
A series of heavy metal complexes of crosslinked chitosans were evaluated by thermogravimetric studies. The metal complexes with Cu, Cd and Hg ions exhibiting the highest complexing ability to chitosans (Hg 354-364, Cu 100-112, and Cd 121-160, in mg/g chitosan), had the lowest onset of degradation temperatures (range 194-210 degrees C) and the lowest final degradation temperatures (generally less than 294-304 degrees C for Hg, 296-338 degrees C for Cu, and 305-368 degrees C for Cd complexes). Mn ion, with the lowest binding to chitosans (Mn 5-7 mg/g), showed the reverse behavior, having onset (240-248 degrees C) and final degradation temperatures (range 300-368 degrees C). Zn (binding 74-87 mg/g) and Pb (binding 39-62 mg/g) ions have a binding ability intermediate to Cu/Cd/Hg and Mn extremes, and therefore the effects on onset and final degradation temperatures are intermediate to these values. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Chitosan; Crosslinked chitosan; Degradation temperature; Metal complexes; Thermal properties; Thermogravimetry

Utilization of sugarcane bagasse cellulose for producing cellulose acetates: novel use of residual hemicellulose as plasticizer - Shaikh, Hamid M.; Pandare, Kiran V.; Nair, Greeshma; Varma, Anjanikumar (Carbohydrate Polymers, 2009)
Sugarcane bagasse was fractionated to cellulose, hemicellulose and lignin by a proprietary steam explosion process, followed by downstream purifications, developed in our laboratory. The fractionated cellulose contained similar to 94% cellulose, about similar to 5% hemicellulose, traces of lignin (similar to 0.2%), and similar to 1% ash. The cellulose was acetylated under heterogeneous conditions to obtain cellulose acetates. These were extensively characterized using FTIR, TGA, DSC, GPC, HPIC, WAXRD, and viscometry. The novel feature of this study was the utilization of the hemicellulose content (5%) of bagasse cellulose as an internal plasticizer. Through kinetic experimentation, we have demonstrated that the residual hemicellulose need not be considered as an impurity; rather it can be used in acetylated form as a plasticizer as well as a biodegradable additive for cellulose acetates made from slightly impure cellulose produced from non-wood origin. Our results therefore show how lignocellulosic agricultural wastes can be utilized to produce high value plastics. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bagasse cellulose; Cellulose acetate; Hemicellulose; Plasticizer; Sugarcane bagasse; Xylan acetate

D-(-)-Lactic acid production from cellobiose and cellulose by Lactobacillus lactis mutant RM2-24 - Singhvi, Mamta; Joshi, Dipti; Adsul, Mukund G.; Varma, Anjanikumar; Gokhale, Digambar V. (Green Chemistry, 2010)
Lactobacillus lactis mutant RM2-24 utilizes cellobiose efficiently, converting it into D-(-)-lactic acid. Cellobiose-degrading enzyme activities were determined for whole cells, cell extracts and disrupted cells. Aryl-beta-glucosidase activity was detected in whole cells and disrupted cells, suggesting that these activities are confined to the cells. The mutant produced 80 g l(-1) of lactic acid from 100 g l(-1) of cellobiose with 1.66 g l(-1) h(-1) productivity. Production of D-lactic acid from different cellulose samples was also studied. The cellulose samples at high concentration (10%) were hydrolyzed by cellulase enzyme preparation (10 FPU g(-1) cellulose) derived from Penicillium janthinellum mutant EU1 generated in our own laboratory. We obtained a maximum 72% hydrolysis, yielding glucose and cellobiose as the main end products. Lactic acid was produced from these cellulose samples by simultaneous sacchari. cation and fermentation (SSF) in a media containing a cellulase enzyme preparation derived from Penicillium janthinellum mutant EU1 and cellobiose utilizing Lactobacillus lactis mutant RM2-24. A maximum lactic acid concentration of 73 g l(-1) was produced from a concentration of 100 g l(-1) of bagasse-derived cellulose, the highest productivity and yield being 1.52 g l(-1) h(-1) and 0.73 g g(-1), respectively. Considering that bagasse is a waste material available in abundance, we propose to use this biomass to produce cellulose and then sugars, which can be fermented to valuable products such as ethanol and lactic acid.

Production of single cell protein, essential amino acids, and xylanase by penicillium janthinellum - Rao, Mala; Varma, Anjanikumar; Deshmukh, Sumedha S. (Bioresources, 2010)
Microbial biomass having 46% crude protein content and enriched with essential amino acids as well as extracellular xylanase activity (100-150 IU/ml) was produced by an efficient fungal strain, Penicillium janthinellum (NCIM St-F-3b). Optimization studies for maximum xylanase and biomass production showed that the fungus required a simple medium containing bagasse hemicellulose as carbon source and ammonium sulphate as the nitrogen source. Therefore bagasse, which is a waste product of the sugar industry, can be efficiently used in microbioal biomass protein preparation for animal feed.
Keywords: Bagasse hydrolysate; Crude protein; Microbial biomass production; Penicillium janthinellum; Xylanase

Enhanced enzymatic hydrolysis of cellulose by partial modification of its chemical structure - Shaikh, H. M.; Adsul, Mukund G.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2011)
A series of 2,3-dialdehyde celluloses with different degrees of oxidation were used for deriving corresponding dicarboxylate, dicarboxy, and Schiff's base cellulose derivatives. The dialdehyde cellulose was hydrolyzed by cellulase to a lower extent than the starting cellulose, except at high levels of aldehyde content (above 50%). For dicarboxylate and dicarboxy celluloses, the highest level of oxidized NaDCC and DCC hydrolysed up to 70 and 60% respectively which was 3-4 times more than cellulose. The 2,3-dioxime cellulose derivative hydrolyzes only up to 16.3% for the highest level of oxidized dioxime. In the case of 2,3-diethylimine cellulose, all derivatives hydrolyse faster than the native cellulose. Up to 75% hydrolysis was observed for 2,3-diethyimine cellulose-50, 2,3-dipropylimine and 2,3-dibutylimine cellulose. The 2,3-dibenzylimine cellulose hydrolyses a little slower than the alkylimine derivatives. The 2,3-dihydrazone cellulose derivatives with all level of oxidation showed resistance towards enzymatic hydrolysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 3-Dialdehyde celluloses; 3-Dibenzylimine cellulose; 3-Dibutylimine cellulose; 3-Dicarboxy celluloses; 3-Diethyimine cellulose; 3-Dihydrazone cellulose; 3-Dipropylimine cellulose; Cellulase; Enzymatic hydrolysis

Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose

Towards biodegradable elastomers: green synthesis of carbohydrate functionalized styrene-butadiene-styrene copolymer by click chemistry - Singh, Rakesh; Varma, Anjanikumar (Green Chemistry, 2012)
Random attachment of sugar molecules to synthetic polymers is an important strategy to induce biodegradability in these polymers. The present study successfully employs ``click'' chemistry to introduce low levels of sugar molecules onto styrene-butadiene-styrene (SBS) copolymer, a widely used commodity polymer which is not biodegradable. Spectral, morphological and thermal studies of the modified polymers were carried out to show the dramatic changes in the properties of these modified polymers. Thermal stability of glucose linked SBS had onset of degradation at 428 degrees C, down from 478 degrees C observed for SBS. Morphology studied by WAXRD and SEM showed destructuring of the polymer domains of SBS, which is beneficial for biodegradation of these polymers. Previous studies showed that sugars anchored by hydrolysable ester groups onto polystyrene were biodegradable; current studies show that sugars anchored by unhydrolyzable C-C bonds on the butadiene component of SBS copolymer are also significantly biodegradable.

Functional nanoparticles obtained from cellulose: engineering the shape and size of 6-carboxycellulose - Sharma, Priyanka R.; Varma, Anjanikumar (Chemical Communications, 2013)
Agricultural residue derived cellulose and cotton cellulose were used to synthesize quasi-spherical nanoparticles of 6-carboxycellulose having diameter 25-35 nm. This provides a new range of functionalized nanostructured celluloses with increased versatility and applications. The nanoparticles were efficient in stabilizing carbon nanotube dispersions and were effective anti-microbial agents against E. coli.

Functionalized celluloses and their nanoparticles: morphology, thermal properties, and solubility studies - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Agricultural residues derived cellulose was used to synthesize a new series of carboxy functionalized cellulosic nanoparticles (quasi-spherical shaped, 13.2-21.5% carboxyl content) and macro-sized 6-carboxycelluloses (long-fibril shaped, 1.7-22% carboxyl content). The DP (50-70) and yield (upto 46%) of nanoparticles were manipulated by controlling the reaction temperature and time. TGA/DTG thermographs of the carboxycelluloses gave thermostability data and co-related well with the residual crystalline, amorphous, and anhydroglucuronic acid content. The particle shape and size had no effect on the thermal stability. Some derivatives were fully or partially soluble in aqueous alkali and non-aqueous solvents, which can lead to increased versatility of these polymers. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 6-Carboxycellulose; cellulose; DTG; Morphology; Nanoparticles; TGA

Supramolecular transitions in native cellulose-I during progressive oxidation reaction leading to quasi-spherical nanoparticles of 6-carboxycellulose - Sharma, Priyanka R.; Rajamohanan, Pattuparambil R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Cellulose-I swells considerably in phosphoric acid, and converts to amorphous cellulose via a cellulose-II transition state. Controlled oxidation of cellulose-I to 6-carboxycellulose (6CC) using HNO3-H3PO4-NaNO2 oxidation system led to the selective production of 6CC's of varying carboxyl contents (1.7-22%) as well as various shapes and sizes (macro-sized fibrils of several micron length and/or spherical nanoparticles of 25-35 nm), depending on the reaction conditions. 6CC's having less than 14% carboxyl content were largely in cellulose-II form (WAXRD values in-between cellulose I and cellulose II), whereas at 14-22% the 6CC's were largely amorphous; only trace crystallinity was observed at 19% and 22% carboxyl 6CC. Spherical nanoparticles retained a high degree of crystallinity having cellulose-I structure, whereas the macro-sized fibrils were largely converted to cellulose-II structure. Analysis by WAXRD as well as by CP-MAS C-13 NMR studies gave similar conclusions. Reduced molecular weight with progressive oxidation, including presence of oligomers, was also evident from an increase in the reducing-end carbon peak at similar to 92 ppm. For high oxidation levels (>14%) the NMR 92-96 ppm peaks disappeared on extracting with dilute alkali, due to soluble oligomers being removed. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carboxycellulose; cellulose; Nanoparticles; NMR; WAXRD

Thermal stability of cellulose and their nanoparticles: Effect of incremental increases in carboxyl and aldehyde groups - Sharma, Priyanka R.; Varma, Anjanikumar (Carbohydrate Polymers, 2014)
Oxidized cellulose containing carboxyl and aldehyde functional groups represent an important class of cellulose derivatives. In this study effect of incrementally increasing COOH and CHO groups at C2, C3, and C6 positions of cellulose and nanocellulose has been investigated, with a view to understanding their effect on thermal treatment of cellulose. The results show that 2,3-dialdehyde cellulose (DAC) is the most thermally stable oxidized product of cellulose while the most unstable derivatives contain carboxyl group at the C6 position (6CC). Carboxymethylcellulose (CMC), with carboxymethyl group on C6 position, is more stable than 6CC. Multi-functionalized celluloses 2,3,6-tricarboxycellulose and 6-carboxy-2,3-dialdehyde, have the same level of thermal stability as 6CC, showing that the presence of carboxyl at the C6 is a key destabilizing factor in the thermal stability of oxidized cellulose products. More the number of reducing end groups on the polymer chain, lower the thermal stability of the cellulose, as proved by comparing the TGA/DTG of monomeric analogs dextrose, cellobiose and glucuronic acid with the oxidized celluloses. The thermal stability trend observed for oxidized celluloses was DAC > DCC > nanoparticles > dextrose >glucuronic acid, caused by extent of reducing ends and COOH groups. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 2; 3; 3-Dialdehyde cellulose; 6-Carboxycellulose; 6-Tricarboxycellulose; cellulose; TGA/DTG

Effect of mixed acid catalysis on pretreatment and enzymatic digestibility of sugar cane bagasse - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod; Trimukhe, K. D.; Varma, Anjanikumar; Padmanabhan, Sasisanker (Energy & Fuels, 2016)
Aqueous pretreatment using homogeneous acid catalyst is considered as a low-cost technology in the production of lignocellulosic bioethanol. To establish the synergism of mixed acids, pilot-level aqueous pretreatments of bagasse covering a wide range of combined severity (CS) were carried out. To investigate the effect of application of mixture of acids on xylose hydrolysis as well as glucose hydrolysis via pretreatment and enzymatic hydrolysis, the following three combinations of acids were explored: (1) oxalic acid + sulfuric acid (organic + mineral acid), (2) phosphoric + sulfuric acid (mineral acids), and (3) ferric chloride + sulfuric acid (Lewis acid with a mineral acid). Of the pretreatments evaluated, the synergism was most pronounced for the combination of sulfuric and phosphoric acid, which resulted in more than 90% conversion of hemicellulose to xylose and 70% conversion of cellulose to glucose through enzymatic hydrolysis. Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl (S/G) ratio for sulfuric and phosphoric acid combination pretreatment, leading to higher enzymatic conversion. FTIR and dynamic light scattering (DLS) experiments conducted on pretreated sugar cane bagasse provided useful correlation with regard to the pretreatment type, particle size, and enzymatic hydrolysis.

Shape and size engineered cellulosic nanomaterials as broad spectrum anti-microbial compounds - Sharma, Priyanka R.; Kamble, Sunil; Sarkar, Dhiman; Anand, Amitesh; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2016)
Oxidized celluloses have been used for decades as antimicrobial wound gauzes and surgical cotton. We now report the successful synthesis of a next generation narrow size range (25-35 nm) spherical shaped nanoparticles of 2,3,6-tricarboxycellulose based on cellulose I structural features, for applications as new antimicrobial materials. This study adds to our previous study of 6-carboxycellulose. A wide range of bacteria such as Escherichia coli, Staphloccocus aureus, Bacillus subtilis and Mycobacterium tuberculosis (non-pathogenic as well as pathogenic strains) were affected by these polymers in in vitro studies. Activity against Mycobacteria were noted at high concentrations (MIC99 values 250-1000 mu g/ml, as compared to anti-TB drug Isoniazid 0.3 mu g/ml). However, the broad spectrum activity of oxidized celluloses and their nanoparticles against a wide range of bacteria, including Mycobacteria, show that these materials are promising new biocompatible and biodegradable drug delivery vehicles wherein they can play the dual role of being a drug encapsulant as well as a broad spectrum anti-microbial and anti-TB drug. (C) 2016 Published by Elsevier B.V.
Keywords: Anti-microbial; cellulose; Spherical nanoparticles; Tricarboxycellulose

Ethoxy-ester functionalized imidazolium based ionic liquids for lithium ion batteries - Nirmale, Trupti; Khupse, Nageshwar; Gore, Rohitkumar; Ambekar, Jalindar; Kulkarni, Milind; Varma, Anjanikumar; Kale, Bharat (ChemistrySelect, 2018)
Ethoxy ester functionalized imidazolium and bis(tri fluoromethanesulfonyl)imide based ionic liquids (ILs) are synthesized and considered as electrolyte for lithium ion batteries. The series of ethoxy ester functionalized ionic liquids were chosen with increase in ethoxy unit from one to three, followed by polymeric units. These ionic liquids provide both ester and ethoxy groups as interaction sites for Li+ ions enhancing the Li+ ion transportation, resulting in ionic conductivity of 10(-3) Scm(-1) at 25 degrees C, which is of 10(3) factor higher than ethoxy containing polyethylene oxide solid polymer electrolyte. It's noteworthy that the conductivity increases as ethoxy units are increased from one to three units, followed by a decrease for the polymeric ethoxy unit. Electrochemical stability window of these ionic liquids improves as the ethoxy groups are added to imidazolium cation. The Li/LiFePO4 cell fabricated with [ME(3)AMIm][TFSI] electrolyte shows good initial discharge capacity of 98.5 mAhg(-1) at 0.05 C-rate at room temperature, which gradually decreases with cycling. Systematic investigation of electrode surfaces by using SEM and EDX shows deposition of passivation layers on their surfaces. Ionic liquids fabricated by this facile method provide a promising model system for understanding the molecular interactions in promoting the lithium-ion conduction mechanism. The advantages and the limits associated to series of ionic liquid electrolytes are critically investigated.